2005
DOI: 10.1007/s10641-004-2588-z
|View full text |Cite
|
Sign up to set email alerts
|

Competition for food between an introduced crayfish and two fishes endemic to the Colorado River basin

Abstract: SynopsisCrayfish are not native to the Colorado River basin (CRB), however they are now established in portions of the mainstem and in many tributaries. I used density manipulation experiments in a laboratory setting to determine intra-and interspecific competition for food between Orconectes virilis, an aggressive polytrophic crayfish now common in the CRB, and two native fishes: Gila chub, Gila intermedia, and flannelmouth sucker, Catostomus latipinnis. I tested each fish species in separate trials. Growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…Contrasting previous studies have reported that invasive crayfish can affect benthic fish density (Wilson et al 2004, Carpenter 2005, Hirsch and Fischer 2008 or do not have any significant influence on littoral fish (Ruokonen et al 2012). Thus effects on littoral benthic fish communities probably can be expected to vary considerably, depending on the density and size structure of the crayfish population, the fish species present, and the littoral habitat structure.…”
Section: Temporal Effects Of Signal Crayfish On Littoral Macroinvertementioning
confidence: 71%
“…Contrasting previous studies have reported that invasive crayfish can affect benthic fish density (Wilson et al 2004, Carpenter 2005, Hirsch and Fischer 2008 or do not have any significant influence on littoral fish (Ruokonen et al 2012). Thus effects on littoral benthic fish communities probably can be expected to vary considerably, depending on the density and size structure of the crayfish population, the fish species present, and the littoral habitat structure.…”
Section: Temporal Effects Of Signal Crayfish On Littoral Macroinvertementioning
confidence: 71%
“…They also are able to successfully compete with native fishes for food and cover (Carpenter 2005;Arizona Game and Fish Department 2006;USDI Geological Survey 2006).…”
Section: Fish Species Historymentioning
confidence: 99%
“…Native fish may interact with native crayfish in several ways, including predation and competition for resources, directly or through altering habitats or food-webs, resulting in broad impacts on littoral communities. Carpenter (2005) showed that when Orconectes virilis was introduced to the Colorado River basin, native fish growth was reduced as a result of competition for food, but crayfish were not themselves affected. Kirk and Smock (2000) noted the effect of size on competitive outcomes for shelter between the crayfish Cambarus longulus and a megalopteran larva.…”
Section: Interactions Between Indigenous Crayfish Species (Ics) and Fishmentioning
confidence: 99%